Rediscovering Paulo Freire's Pedagogy of Hope - Vílchez Quesada, Enrique (2021)
This essay rediscovers an important work of the Latin American thinker Paulo Freire called Pedagogy of Hope: Reliving Pedagogy of the Oppressed that he published in 1992. After having been subject to intense ideological and political persecution in his country of origin Brazil and in exile, Paulo Freire, with a full maturity granted by years and experience, redefines in the Pedagogy of Hope, the principles of his Pedagogy of the Oppressed, being a faithful witness of the praxis aimed at the emancipation of the oppressed and of the oppressor. This essay recounts, in a contemporary framework, the main reflections evoked by Freire with the hope of rehabilitating in the educational act, and its essential role as an engine of change, a disregard of the truth, which is an indispensable resource towards the search for social justice.